EVALUASI RESISTANSI SENSITIVITAS MODUL GALVANIC SKIN RESPONSE BERBASIS ARDUINO NANO - Rachmat, Hendi Handian; Say, Marinus Moang Laurentius (Jurnal Media Elektro, 2023)
In this study, we evaluated the sensitivity of a Galvanic Skin Response (GSR) sensor to measure human stress levels based on skin conductivity of two fingers. The goal of this evaluation was to define the optimum sensitivity resistance of the Wheatstone bridge circuit in the GSR sensor to detect six different levels of human stress conditions, ranging from Normal level (0–0.415μSiemens) to Severe level (>4.166μSiemens). To perform this evaluation, we designed and implemented the GSR sensor, which consists of a pair of finger electrodes, a voltage divider circuit, a Wheatstone bridge circuit, an instrumentation amplifier, an Arduino Nano controller circuit, and a display module. The evaluation tested four different sensitivity resistances of the Wheatstone bridge circuit: 50kΩ, 100kΩ, 150kΩ, and 200kΩ. Digital values were measured and calculated for each sensitivity resistance when measuring skin resistance values from 0Ω to 30MΩ with a 50kΩ step increment. These values simulated all six stress level conditions. The measurement showed that the sensitivity resistances of 200kΩ, 150kΩ, 100kΩ, and 50kΩ resulted in a range of skin resistances (with an average percentage relative error) of 3MΩ - 250kΩ (0.45%), 3MΩ - 200kΩ (1.06%), 3MΩ - 150kΩ (1.29%), and 2.4MΩ - 100kΩ (1.09%), respectively.